Characterization and preliminary safety evaluation of mycoprotein from Fusarium compactum MM-135 - Yibo Xian; Luqin Yin; Zebin Wu; Dunwu Chen; Zhenhui Sun; Xianzhi Jiang; Lingzhi Tian (Frontiers in Sustainable Food Systems)
IntroductionAlternative protein sources are urgently needed to address the environmental, ethical, and health challenges associated with traditional livestock-derived proteins. Mycoprotein, produced by fermenting filamentous fungi, is a high - quality option with meat - like texture, high protein content, rapid growth, low cost, and environmental sustainability, showing great potential to replace conventional proteins. However, both the research endeavors in the field of mycoprotein and the strain resources employed for mycoprotein production remain relatively scarce.MethodsIn this study, we identified Fusarium compactum MM-135, which was isolated from a humus soil sample in Shennongjia, China. This strain was recognized as a high-performing mycoprotein producer through rapid screening of over 270,000 microbial samples. The protein, fiber, fat, and allergen levels of the mycelium were analyzed biochemically. True protein digestibility (TD) and Protein Digestibility-Corrected Amino Acid Score (PDCAAS) were assessed according to AOAC Official Method 991.29 and FAO/WHO guidelines. Safety evaluations included mycotoxin analysis via HPLC-MS and toxicological tests (Ames, in vivo micronucleus, in vitro chromosome aberration) following the OECD Guidelines. A 14-day dietary study in rats evaluated potential adverse effects at intake levels up to 150,000 ppm, following a modified study protocol and relevant SOPs based on the OECD Guidelines.ResultsThe strain produces mycelium with over 50% protein content, high fiber, low fat, and no allergens. It exhibits TD of 90.79% and a PDCAAS value of 1.00 for children aged 3-10 years and adults. Safety assessments revealed undetectable levels of most mycotoxins. The mycoprotein showed no mutagenicity or genotoxic effects in the Ames assay, in vivo mammalian erythrocyte micronucleus test, and in vitro mammalian chromosome aberration test. A 14-day dietary exposure study in rats demonstrated no adverse effects at intake levels up to 150,000 ppm, providing a strong basis for ongoing 90-day extended toxicity studies.DiscussionThis study highlights F. compactum MM-135 as a viable and sustainable protein source for future food systems, offering a robust solution to meet global protein demands while mitigating environmental impacts.